The Role of Animation in Consumers Attitude Formation: Based on the Tripartite Attitudinal Model (International Journal of Scientific Research and Management (IJSRM), 2017)
This study examines the effects of animation and its relationship to cognitive and affective processes and conation responses by conducting an experimental study. The results of a multi-group confirmatory factor analysis comparing a low-involvement product type and high-involvement product type and in high- and low-involvement contexts revealed a significant group difference on each path regarding values of modification indexes. The study confirmed that the tripartite attitudinal model (for example, cognition, affection and conation) would more effectively work under the low-involvement product type in a highly involved group. This study significantly contributes to our understanding of the relationship between animated commercials and cognitive and affective processing. Animated commercials stimulate viewers or affect their emotional responses and behavioral expectations.